2021
DOI: 10.3389/fimmu.2021.763067
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 26A1 Modulates the Polarization of Uterine Macrophages During the Peri-Implantation Period

Abstract: Uterine M1/M2 macrophages activation states undergo dynamic changes throughout pregnancy, and inappropriate macrophages polarization can cause adverse pregnancy outcomes, especially during the peri-implantation period. Our previous studies have confirmed that Cytochrome P450 26A1 (CYP26A1) can affect embryo implantation by regulating uterine NK cells and DCs. The aim of this study was to investigate whether CYP26A1 regulates the polarization of uterine macrophages in early pregnancy. Here, we observed that Cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These results indicate that CYP26A1 may regulate embryonic implantation via a non‐RA pathway. Recently, we found that CYP26A1 regulates the differentiation of DCs (through CD86 and ID2), polarization of uterine macrophages, and proportion of NK cells during the peri‐implantation period in mice 21–23 . We hence conclude that CYP26A1 affects embryo implantation through immune cells at the maternal‐foetal interface.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These results indicate that CYP26A1 may regulate embryonic implantation via a non‐RA pathway. Recently, we found that CYP26A1 regulates the differentiation of DCs (through CD86 and ID2), polarization of uterine macrophages, and proportion of NK cells during the peri‐implantation period in mice 21–23 . We hence conclude that CYP26A1 affects embryo implantation through immune cells at the maternal‐foetal interface.…”
Section: Discussionmentioning
confidence: 65%
“…Our previous work has found that CYP26A1 shows a peculiar temporal and spatial expression pattern in mice and rats during the peri‐implantation period 19,20 . In Cyp26a1‐MO‐treated and pCR3.1‐Cyp26a1 plasmid‐immunized mice, the number of implantation sites significantly decreases and the proportion of NK cells, dendritic cells (DCs) and macrophages changes dramatically 21–23 . dNK1 cells that highly express CYP26A1 have been identified during early gestation in humans 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this study failed to prove that STAP1 regulate microglia toward an M1-like phenotype. Therefore, the evidence that STAP1 is a marker of the M1-like phenotype [ 36 ] is insufficient. The increased STAP1 expression in the previous study may be because STAP1 can attenuate proinflammatory responses to form negative feedback regulation.…”
Section: Discussionmentioning
confidence: 99%